Modeling of islanding detection methods for microgrid - Sapar, Ahmad Farid (2016)
The increase in world demand for energy as well as environmental concern over scarce and limited fossil fuels has significantly triggered the search for environmentally friendly and renewable energy resources. In Malaysia, the system maximum demand in Peninsular has increased 4.65% from the year 2012 to 16,562 MW which has been recorded in May 13, 2013. Hence, to meet future energy requirement, some proactive measures of alternatives or renewable sources of energy must be established. In this context, the Micro-Grid (MG) concept is the potential solution to the issue of scarce natural resources. However, one of the major challenges associated with implementation of MG is to design an appropriate protection scheme which can protect MG in both grid and islanded mode. Considering this, a MG microswitch-based OUV and OUF IDMs through passive, Non-Intelligent IDM techniques was modelled and simulated. Microswitch-based performance testing has been carried out on both grid-connected and island modes, and considering the active power flow between the two systems and accompanying with different faulty conditions on each case and tested it five simulation cases based on the IEEE Standard 1547.4 test systems. These models were also tested with two fault of conditions in IEEE 15-bus radial distribution test system. The investigation from both test systems shows that, the proposed microswitch-based is effectively to perform in grid-connected and islanded modes. It also could import, export and isolate the active power flow without any serious effect in feeding the Unintentional Islanding Test Load and it function effectively under different faulty. Finally, the implemented concept of microswitch-based on MG is recommended to represent actual Malaysian distribution network model and parameters.